2020
DOI: 10.1038/s41598-020-77612-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Xanthomonas fragariae in strawberry leaves

Abstract: Xanthomonas fragariae is a quarantine bacterial pathogen that causes angular leaf spot on strawberry. The aim of our study was to analyse the mechanism of interaction of this bacterium with its host plant at the transcriptome level. For this purpose, mRNAs of X. fragariae growing in Wilbrink’s medium and from infected strawberry cv. Elsanta plants were isolated and sequenced using the Illumina MiSeq platform. The expression profiles of the bacteria in Wilbrink’s medium and in planta were very diverse. Of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In particular, we found that CRs with increased expression in planta , and particularly those required for full bacterial virulence, belonged to high-DPS clusters ( Table 2 ). This list includes CRs that are upregulated in Dickeya dadantii 3937 and Pectobacterium carotovorum WPP14, two soft-rot bacterial strains ( 39 ); Dickeya dianthicola RNS04.9, which grows on macerated potato tubers ( 40 ); and Xanthomonas fragariae , which grows on strawberry leaves ( 41 ). Similarly, we found several CRs with very high DPS values (80%) that were shown to be relevant in Xanthomonas citri virulence ( 42 ) or required for fitness of Pseudomonas savastanoi pv.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we found that CRs with increased expression in planta , and particularly those required for full bacterial virulence, belonged to high-DPS clusters ( Table 2 ). This list includes CRs that are upregulated in Dickeya dadantii 3937 and Pectobacterium carotovorum WPP14, two soft-rot bacterial strains ( 39 ); Dickeya dianthicola RNS04.9, which grows on macerated potato tubers ( 40 ); and Xanthomonas fragariae , which grows on strawberry leaves ( 41 ). Similarly, we found several CRs with very high DPS values (80%) that were shown to be relevant in Xanthomonas citri virulence ( 42 ) or required for fitness of Pseudomonas savastanoi pv.…”
Section: Resultsmentioning
confidence: 99%
“…Xanthomonas fragariae is a gram-negative bacterium that causes angular spotting of strawberry leaves and is listed in Europe as a quarantine pathogen in the EPPO A2 list (Puławska et al, 2020). This is a potentially serious and insidious disease, first reported in the United States.…”
Section: Angular Leaf Spot (Xanthomonas Fragariae)mentioning
confidence: 99%
“…The virulent Xaf strain LMG25863 was predicted to contain twenty-three T3Es and several putative new effectors (Vandroemme et al, 2013). Furthermore, transcriptome analysis of Xaf in strawberries revealed that T3Es can be functional in Xaf during the pathogenesis process (Gétaz et al, 2020; Puławska et al, 2020). Recently, 47 T3Es were mined based on a machine-learning method, and two novel Xaf T3Es, XopBG and XopBF, were translocated and elicited hypersensitive reaction (HR) on pepper leaves, revealed its possible pathogenic role in Xaf Fap21 (Wagner et al, 2023).…”
Section: Introductionmentioning
confidence: 99%